Investigation of the Unsteady External and Underhood Airflow of the DrivAer model by Dynamic Mode Decomposition Methods - Daiki Matsumoto; Lukas Haag; Thomas Indinger (International Journal of Automotive Engineering, 2017)
In this research, we conduct unsteady CFD to investigate the effect of engine bay flow on the steady and unsteady aerodynamics of the extended DrivAer model reproducing engine bay flow. Dynamic Mode Decomposition (DMD) is performed to analyze unsteady aerodynamics. As a result, it is revealed that different engine bay setups results in not only differences of steady aerodynamics but also the differences of unsteady aerodynamic characteristics. Furthermore, we perform an on-the-fly algorithm of DMD called Streaming Total DMD (STDMD) which can be conducted with much less memory than conventional DMD to investigate the relevancy and applicability of STDMD on the analysis of unsteady aerodynamics of a road vehicle.